2010
DOI: 10.1590/s0100-67622010000500008
|View full text |Cite
|
Sign up to set email alerts
|

Leucaena leucocephala (Lam.) de Wit (Fabaceae): invasora ou ruderal?

Abstract: José Nicola Martorano Neves da Costa 2 e Giselda Durigan 3 RESUMO -(Leucaena leucocephala (Lam.) de Wit (Fabaceae): invasora ou ruderal?). A utilização de espécies exóticas em plantios de recuperação de áreas degradadas tem sido condenada com base no argumento de que tais espécies podem se comportar como invasoras e contaminar os ecossistemas naturais ao redor das áreas onde forem plantadas. Leucaena leucocephala (leucena) é espécie leguminosa exótica que tem sido frequentemente cultivada no Brasil para recupe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
12

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 23 publications
0
15
0
12
Order By: Relevance
“…Even though Leucaena is a species applied in reforestation and/or feeding cattle under semiarid regions, they can be troublesome for farmers during maize development. Costa and Durigan (2010) conducted a study evaluating if L. leucocephala acts as a weed disturbing environmental equilibrium or not. They concluded that L. leucocephala was a weed.…”
Section: Discussionmentioning
confidence: 99%
“…Even though Leucaena is a species applied in reforestation and/or feeding cattle under semiarid regions, they can be troublesome for farmers during maize development. Costa and Durigan (2010) conducted a study evaluating if L. leucocephala acts as a weed disturbing environmental equilibrium or not. They concluded that L. leucocephala was a weed.…”
Section: Discussionmentioning
confidence: 99%
“…em todas as áreas, independentemente do modelo de PRAD adotado, pode ser explicada pelo comportamento ecológico de rápido crescimento e dispersão da espécie e pela localização, nas áreas adjacentes, de plantios homogêneos dessa espécie. Espécies exóticas podem comprometer a restauração de áreas degradadas, pois algumas são de difícil controle e interferem no processo sucessional das espécies nativas (Costa & Durigan, 2010). De acordo com Assis et al (2013), embora existam instrumentos legais para a regularização do uso de espécies exóticas, ainda é frequente o plantio desse tipo de espécie em áreas de PRAD.…”
Section: Resultsunclassified
“…The presence of this species is widely discussed in the literature. The species is frequently considered aggressive, inhibitor, invasive, or ruderal Durigan, 2010;Fonseca;Jacob, 2011;Walker, 2011;Kebede, 2016). According to Lowe et al (2000), L. leucocephala was included in the International Union for Conservation of Nature -IUCN list of the 100 world's worst invasive alien species.…”
Section: Discussionmentioning
confidence: 99%